The Adoption of Technology Acceptance Model in E-commerce with Artificial Intelligence as a Mediator - Aram Massoudi; Muslim N. Zaidan; Azwar Qasim Agha (GECONTEC: Revista Internacional de Gestión del Conocimiento y la Tecnología)
The rapid advancement of technology has significantly changed how consumers approach their purchasing habits. The global volume of online commerce has seen a significant surge, largely due to the COVID-19 pandemic, which has accelerated the growth of e-commerce. Increasingly, online merchants are incorporating cutting-edge Artificial Intelligence technology into their platforms to better grasp customer needs and enrich the shopping journey. However, there has been little research conducted on how consumers adapt to and utilize artificial intelligence powered online stores. This study seeks to examine the connection between the elements of the Technology Acceptance Model and E-commerce, with artificial intelligence serving as a mediator in this relationship. A survey was conducted with 352 Iraqi participants who participate in online shopping. Structural equation modelling was applied for data analysis. After establishing the initial theoretical model, a nested model based on TAM was formulated and examined. The finding showed that both ease of use and usefulness as a TAM component positively influences the likelihood of AI adoption and continued usage among online shoppers. Also, artificial intelligence has a positive influence on the customers’ adoption of E-commerce. Finally, artificial intelligence plays a mediate role between Technology Acceptance Model and E-commerce. These results offer valuable insights for online retailers looking to improve customer adoption of AI technologies.